2007
DOI: 10.1002/app.26298
|View full text |Cite
|
Sign up to set email alerts
|

Novel modification of cyanate ester by epoxidized polysiloxane

Abstract: A novel modification of cyanate ester (CE) resin by epoxidized polysiloxane (E-Si) has been developed, and the modified system is coded as CE/E-Si. E-Si was prepared by the reactions among octamethylcyclotetrasiloxane, hexamethyldisiloxane, (3-aminopropyl)-methyldiethoxysilane, and diglycidyl ether of bisphenol-A resin. Six formulations were designed to evaluate the effect of the weight ratio between CE and E-Si on performance parameters. Results reveal that the addition of E-Si in CE resin cannot only signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…For inorganic fillers-filled polymeric composites, the conclusion of the fillers effect on the thermodegradation of the composites is not consistent with each other. For example, Gu and coworkers developed a novel CE resin modified by epoxidized polysiloxane (E-Si), coded as CE/E-Si; their investigations on thermal property showed that the glass transition temperature and initial degradation temperature of CE/E-Si system were lower than that of the original CE resin 15 ; similarly, study by Koo et al concluded that the incorporation of nano-SiC whiskers did not enhance the thermal stability of CE resin. 18 However, some researchers came out with contrary researches.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For inorganic fillers-filled polymeric composites, the conclusion of the fillers effect on the thermodegradation of the composites is not consistent with each other. For example, Gu and coworkers developed a novel CE resin modified by epoxidized polysiloxane (E-Si), coded as CE/E-Si; their investigations on thermal property showed that the glass transition temperature and initial degradation temperature of CE/E-Si system were lower than that of the original CE resin 15 ; similarly, study by Koo et al concluded that the incorporation of nano-SiC whiskers did not enhance the thermal stability of CE resin. 18 However, some researchers came out with contrary researches.…”
Section: Introductionmentioning
confidence: 94%
“…11,12 To date, some inorganic/CE hybrids have been studied, such as aluminum borate whisker/CE, polyhedral oligomeric silsesquioxanes/CE, and epoxidized polysiloxane/CE. [13][14][15] Results have proved that hybrids have better properties than original CE resin, and the properties of inorganic/CE hybrids are greatly depending on the property of inorganic materials. The properties of present inorganic/CE hybrids need to be further improved.…”
Section: Introductionmentioning
confidence: 98%
“…octamethylcyclotetrasiloxane (Me 2 SiO) 4 (D 4 ) with carbofunctional disiloxanes, which are carried out in acidic or basic media (Scheme 2) (Yilgor & McGrath, 1988;Harabagiu et al, 1996). For example, by the equilibration of D 4 (D = Me 2 SiO) with (3-aminopropyl)methyldiethoxysilane and hexamethyldisiloxane Me 3 SiOSiMe 3 , polydimethyl-co-[(aminopropyl)(methyl)]-siloxane oils (containing side aminopropyl groups) were prepared (Yang et al, 2007).…”
Section: Synthesis Of Cfpsmentioning
confidence: 99%
“…The carbofunctional polysiloxanes, in which alkylfunctional groups are attached to the silicon atoms inside of the polymer chain were also prepared by the catalytic equilibration of cyclotetrasiloxane, containing aminopropyl functional groups (D 3 D NH2 ), with decamethyltetrasiloxane MD 2 M (D = Me 2 SiO, M = Me 3 SiO 0.5 ) in the presence of Me 4 NOSiMe 3 (TMAS) (Zhou et al, 2004;Yang et al, 2007) Scheme 3. The preparation of CFPS with pendant aminopropyl functional groups.…”
Section: Synthesis Of Cfpsmentioning
confidence: 99%
“…Among them, the modification of BCE resin by epoxy (EP) resin has proved to be an effective route, which not only effectively improves the toughness, but also reduces high curing temperature of BCE. However, compared with pristine BCE resin, EP/BCE resin has declined heat resistance and poorer dielectric properties 11. These flaws limit the widespread application of cured EP/BCE resins.…”
Section: Introductionmentioning
confidence: 99%